Hydatid disease of proximal femur: a case report - Swaroop Chandra, S.; Mohan Kumar, M.; ., Ramnarayanan; Vanchi, Pravin K. (International Journal of Research in Orthopaedics, 2017)
Hydatid disease is the most common infection in Central Asia, Middle East, East Africa caused by Echinococcus which is a cestode. However infection to bone alone is very rare. We report a case of Hydatid cyst in bone parse. A 55 years old lady came with a complaint of pain over right hip since 1 year. Radiologically found to be having osteolytic lesion over proximal femur for which surgery was done and biopsy report showed hydatid cyst. The case is reported for its rarity.